Playing at altitude. Performance of a Mexican professional football team at different level of altitude - Alanis, A.; Salas, O.; Salas, K.; Quintero, I.; Carranza, Y.; Salazar, L. (Apunts Sports Medicine, 2022)
Background: Football is the most popular sport in the world, and matches are commonly played at different levels of altitude. As the altitude increases, the availability of oxygen decreases. The dynamics of the ball will be altered due to the decrease in air resistance. These conditions can affect the physical and/or sports performance of football players. The objective of this study is to determine if there is a relationship between altitude and performance of a professional football team. Methods: A total of 130 matches of a Mexican professional football team were analyzed. Physical performance was measured by Match Analysis®, a video and statistical analysis; sports performance was measured according to the score. Altitude was measured with Geo Elevation. Results: No relationship was found between altitude and total distance covered (p=0.165), Distance in first half (p=0.441) sprints number(p=0.115) and time between sprints (p=0.237)